Réponses

2014-06-04T13:22:45+02:00
Bonjour,

Anatol a tort.

On utilise la formule (a - b)² = a² - 2ab + b²

n^2-24n+144=n^2-2\times n\times12+12^2\\n^2-24n+144=(n-12)^2\\\\n^2-24n+144=0\Longleftrightarrow (n-12)^2=0\\n^2-24n+144=0\Longleftrightarrow n-12=0\\\boxed{n^2-24n+144=0\Longleftrightarrow n=12}

Donc n²-24n+144 peut être égal à 0 si n = 12.
Meilleure réponse !
  • Utilisateur Brainly
2014-06-04T14:38:03+02:00
N² - 24n + 144 = (n - 12)²

(n - 12)² = 0
n - 12 = 0
n = 12

Donc il a tort puisque n² - 24n + 144 = 0 pour n = 12